Biogeophysical Impacts of Land‐Use Change on Climate Extremes in Low‐Emission Scenarios: Results From HAPPI‐Land. Issue 3 (8th March 2018) - Hirsch, Annette L.; Guillod, Benoit P.; Seneviratne, Sonia I.; Beyerle, Urs; Boysen, Lena R.; Brovkin, Victor; Davin, Edouard L.; Doelman, Jonathan C.; Kim, Hyungjun; Mitchell, Daniel M.; Nitta, Tomoko; Shiogama, Hideo; et al.
Abstract: The impacts of land use have been shown to have considerable influence on regional climate. With the recent international commitment to limit global warming to well below 2°C, emission reductions need to be ambitious and could involve major land‐use change (LUC). Land‐based mitigation efforts to curb emissions growth include increasing terrestrial carbon sequestration through reforestation, or the adoption of bioenergy crops. These activities influence local climate through biogeophysical feedbacks, however, it is uncertain how important they are for a 1.5° climate target. This was the motivation for HAPPI‐Land: the half a degree additional warming, prognosis, and projected impacts—land‐use scenario experiment. Using four Earth system models, we present the first multimodel results from HAPPI‐Land and demonstrate the critical role of land use for understanding the characteristics of regional climate extremes in low‐emission scenarios. In particular, our results show that changes in temperature extremes due to LUC are comparable in magnitude to changes arising from half a degree of global warming. We also demonstrate that LUC contributes to more than 20% of the change in temperature extremes for large land areas concentrated over the Northern Hemisphere. However, we also identify sources of uncertainty that influence the multimodel consensus of our results including how LUC is implemented and the corresponding biogeophysical feedbacks that perturb climate. Therefore, our results highlight the urgent need to resolve the challenges in implementing LUC across models to quantify the impacts and consider how LUC contributes to regional changes in extremes associated with sustainable development pathways. Plain Language Summary: The motivation for the Intergovernmental Panel on Climate Change Special Report of 1.5°C stems from the need to understand how the impacts of climate change may evolve for half a degree of global warming. Most low‐emission scenarios involve substantial land‐use change (LUC) including the expansion of bioenergy and food crops, as well as afforestation. Future emission scenarios used as input to climate models are derived using integrated assessment models, and focus on greenhouse gas emissions. However, changes in land use also have a direct effect on local climate through the local water and energy balances, which is not considered in these models, and therefore, our understanding on how dependent these climate projections are to the choice of land‐use scenario is limited. Our study demonstrates that the land‐use scenario has a considerable influence on the projections of temperature extremes for low‐emission scenarios. In particular, for large land areas in the Northern Hemisphere, more than 20% of the change in temperature extremes can be attributed to LUC. However, our study also reveals that considerable uncertainty remains on what the feedbacks of land use may mean for land‐based mitigation activities. Key Points: Land‐use change (LUC) accounts for 20% change in temperature extremes for low‐emission scenarios Multimodel results show projected temperature extremes depend on where and what land‐based mitigation activities are pursued For some regions and models, LUC can affect temperature extremes as much as a half degree change in global mean temperature